2007
DOI: 10.1093/jos/ffm018
|View full text |Cite
|
Sign up to set email alerts
|

Coherence and Coreference Revisited

Abstract: For more than three decades, research into the psycholinguistics of pronoun interpretation has argued that hearers use various interpretation 'preferences' or 'strategies' that are associated with specific linguistic properties of antecedent expressions. This focus is a departure from the type of approach outlined in Hobbs (1979), who argues that the mechanisms supporting pronoun interpretation are driven predominantly by semantics, world knowledge and inference, with particular attention to how these are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
377
3
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(460 citation statements)
references
References 33 publications
31
377
3
11
Order By: Relevance
“…However, the prediction about a higher rate of pronominalization for the marked referents is not met, as referents headed by this and so'n tend to be picked up by lexically more elaborated types of noun phrases. This latter finding underlines the necessity to dissociate between likelihood of pronominalization and referential persistence (confirmation of more recent studies conducted by Kehler et al 2008, Chiriacescu & von Heusinger 2010, Kaiser 2010. Overall, the findings of this paper cast new light on the notions of accessibility, activation or prominence operationalized in terms of referential persistence and likelihood of pronominalization as equally weighted factors.…”
Section: [Geben Sie Text Ein]supporting
confidence: 86%
“…However, the prediction about a higher rate of pronominalization for the marked referents is not met, as referents headed by this and so'n tend to be picked up by lexically more elaborated types of noun phrases. This latter finding underlines the necessity to dissociate between likelihood of pronominalization and referential persistence (confirmation of more recent studies conducted by Kehler et al 2008, Chiriacescu & von Heusinger 2010, Kaiser 2010. Overall, the findings of this paper cast new light on the notions of accessibility, activation or prominence operationalized in terms of referential persistence and likelihood of pronominalization as equally weighted factors.…”
Section: [Geben Sie Text Ein]supporting
confidence: 86%
“…Speakers are more likely to mention goals than sources in sentence-continuation tasks (Kehler et al, 2008;Stevenson et al, 1994), and corpus analysis suggests that goals are more likely to be mentioned than sources (Arnold et al, 2000). In the materials we adopted for this task, goals were also rated as more likely to be mentioned .…”
Section: Discussionmentioning
confidence: 99%
“…When the following clause provides an explanation for the scaring event, the expected cause is more likely to be mentioned-that is, it is referentially predictable. Nevertheless, several studies have shown that speakers are no more likely to use pronouns to refer to the implicit cause than the other character, and instead speakers show a general preference to use pronouns for the subject character (Fukumura & van Gompel, 2010;Kehler et al, 2008). Given that acoustic reduction and pronoun use tend to occur in the similar discourse contexts (Ariel, 1990;Arnold, 2008;Gundel et al, 1993), these findings might predict that thematic role predictability would not affect acoustic reduction.…”
Section: Does Thematic Role Predictability Affect Duration?mentioning
confidence: 98%
See 2 more Smart Citations